The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1111/j.1528-1157.1999.tb00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Epileptogenic Zone by Ictal and Interictal SPECT with 99mTc‐Ethyl Cysteinate Dimer in Patients with Medically Refractory Epilepsy

Abstract: Summary:Purpose: To evaluate the accuracy, feasibility and clinical value of both ictal and interictal y9"Tc-ethyl cysteinate dimer (ECD) single photon emission computed tomography (SPECT) in patients with medically refractory epilepsy.Methods: The study included 75 consecutive patients, 48 with temporal lobe epilepsy (TLE group), and 27 with extratemporal epilepsy (ExT group). The accuracy of SPECT was analyzed considering the final diagnosis reached by convergence of clinical, electrophysiologic, structural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
1
21
1
13
Order By: Relevance
“…The sensitivity was higher than that reported by other authors [41, 43]. For example, Dietrich et al [41]disclosed that abnormal regions were detected in 21 of 23 patients with complex partial seizures in a SPECT study, while Oliveira et al [44]reported that ictal SPECT could identify epileptogenic zones in 91.3% of patients as compared with 62.1% for interictal SPECT examination. The different results seen between our study and previous ones may be attributed to several causes, such as (1) differences in seizure type and duration of epilepsy, (2) differences in the criteria applied for detecting abnormalities, and (3) differences in attention to EEG findings.…”
Section: Discussioncontrasting
confidence: 49%
“…The sensitivity was higher than that reported by other authors [41, 43]. For example, Dietrich et al [41]disclosed that abnormal regions were detected in 21 of 23 patients with complex partial seizures in a SPECT study, while Oliveira et al [44]reported that ictal SPECT could identify epileptogenic zones in 91.3% of patients as compared with 62.1% for interictal SPECT examination. The different results seen between our study and previous ones may be attributed to several causes, such as (1) differences in seizure type and duration of epilepsy, (2) differences in the criteria applied for detecting abnormalities, and (3) differences in attention to EEG findings.…”
Section: Discussioncontrasting
confidence: 49%
“…O SPECT ictal, que se mostra mais sensível que o interictal na localização da zona de início das crises, é de obtenção difícil, devido à baixa estabilidade do HM-PAO in vitro. Entretanto, o uso do dimer etil-cisteinato tem permitido a obtenção de SPECTs ictais com maior facilidade, constituindo-se num armamentário importante na definição da zona epileptogênica 65 .…”
Section: ) Diagnóstico Topográfico Neurofisiológicounclassified
“…Bearing in mind the availability and relatively low cost of technetium-99m and the high resolution visualization of Tc-tracers by widely available SPECT-cameras, a technetium-99m labelled compound with the biological characteristics of flumazenil would be an interesting alternative for in vivo visualization of the benzodiazepine receptors in an acute setting analogous to the application of 99m Tc-ECD for the visualization of epileptic foci. 14 The aim of this study was the synthesis and the biological evaluation in mice of …”
Section: Introductionmentioning
confidence: 99%